Today’s Condition and Challenges of Small Business Development - A. P. Garnov; V. Yu. Garnovа; N. P. Tishkina (Вестник Российского экономического университета имени Г. В. Плеханова)
Small business, especially just started, contains a lot of risks and depends greatly on external conditions. To motivate small business development it is necessary to create favorable economic environment. The article makes an interregional comparison of economic conditions required for the development of small and medium entrepreneurship. On the basis of this analysis the authors designed proposals aimed at resolving the most topical problems. They researched key components of state support within the frames of programs being implemented on the territory of Moscow  and the Belgorod region. It was shown that improvement of  regional systems of small and medium business support should aim at creation of favorable conditions for the development of innovation activity of small business. To develop regional programs of small innovation business support it is recommended to use experience of other regions with more developed small business and overseas achievements, for instance, Chinese experience.